The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1161/01.str.0000204184.34946.41
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Is a Mediator of Cerebral Ischemic Damage

Abstract: Background and Purpose-We observed recently that elevated plasma cysteine levels are associated with poor clinical outcome in acute stroke patients. In a rat stroke model, cysteine administration increased the infarct volume apparently via its conversion to hydrogen sulfide (H 2 S). We therefore investigated the effects of H 2 S and the inhibition of its formation on stroke. Methods-Cerebral ischemia was studied in a rat stroke model created by permanent occlusion of the middle cerebral artery (MCAO). The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
192
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(203 citation statements)
references
References 27 publications
8
192
0
3
Order By: Relevance
“…Plasma H 2 S levels in the patients as well as control subjects in our study are comparable with earlier studies which is within the range of 10 to100 micromol/l in human subjects. 5 Elevated hydrogen sulfide levels in plasma were also reported in patients with proliferative diabetic retinopathy 20 as well as patients with cardiovascular disease 21 cerebral ischaemic damage 22 and septic shock 23 M. Yusuf et al has earlier reported that the streptozotocin-induced diabetes in rat is associated with enhanced tissue hydrogen sulfide biosynthesis. 17 The activities of H 2 S producing enzymes and the tissue H 2 S contents are known to increase under diabetic conditions.…”
Section: Resultsmentioning
confidence: 98%
“…Plasma H 2 S levels in the patients as well as control subjects in our study are comparable with earlier studies which is within the range of 10 to100 micromol/l in human subjects. 5 Elevated hydrogen sulfide levels in plasma were also reported in patients with proliferative diabetic retinopathy 20 as well as patients with cardiovascular disease 21 cerebral ischaemic damage 22 and septic shock 23 M. Yusuf et al has earlier reported that the streptozotocin-induced diabetes in rat is associated with enhanced tissue hydrogen sulfide biosynthesis. 17 The activities of H 2 S producing enzymes and the tissue H 2 S contents are known to increase under diabetic conditions.…”
Section: Resultsmentioning
confidence: 98%
“…In an in vivo model for myocardial ischemia-reperfusion, a U-shaped H 2 S dose dependence curve was observed, with the cardioprotective effect of H 2 S decreasing at higher concentrations (7). In a rat model of stroke, administration of high NaHS levels increased infarct volume (42), and H 2 S was found to be proinflammatory in a mouse endotoxic shock model (8). Mutations in CBS are the most common cause of severe hyperhomocysteinemia in comparison with defects elsewhere in the pathway (e.g.…”
mentioning
confidence: 94%
“…For example, Moore et al reported that pre-treatment with Na 2 S at 90 mol/kg administered 10 min before middle cerebral artery occlusion (MCAO) did not affect, whereas at 180 mol/kg aggravated, cerebral injury of rats (8). Ren et al reported that NaHS at 25 mol/kg administered 30 min prior to ischemia, but not at 90 or 180 mol/kg, attenuated neuronal injury induced by global cerebral ischemia (18).…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators have suggested that H 2 S-induced neurotoxicity may be mediated via enhancement of N-methyl-D-aspartate receptor (NMDAR) 2 activity (7-9), because toxicity of H 2 S was abolished by NMDAR antagonist in vitro and in vivo (8,9). Based on these observations, we hypothesized that a hybrid NMDAR antagonist that is capable of slowly releasing H 2 S in circulation is more effective in protecting neurons than H 2 S donor compounds alone.…”
Section: Physiological Levels Of H 2 S Exert Neuroprotective Effectsmentioning
confidence: 99%